Imperial Drug Economies, Development, and the Search for Alternatives in Asia, from Colonialism to Decolonisation - John Collins (Revue Internationale de Politique de Développement)
This paper challenges contemporary policy conceptions on the historical relationship between drugs and development policies. It uses a historical analysis to examine the interaction of drugs, governance, security, welfare and economic development policies within drug producing contexts in Asia, from colonialism through the period of decolonisation. It highlights that although modern narratives of drugs and development tend to view the latter as new and involving even immediately contemporary innovations for dealing with the outcomes of drug economies and drug policies, the historical reality is much more complex. Managing drugs and development was a fundamental historical process of state regulation, control and the settling of geographical boundaries, both economically and physically. This chapter posits two foundational ideas. First, the issues of drugs and development have always been fundamentally linked, from the globalisation of trade through mercantilist imperial policies, state formation, the limits of governance, the distribution of economic gains, and political economy outcomes stretching from the local to the global. Drugs, licit and illicit, have therefore always been an issue of economic development. Second, policymakers have long recognised and developed state responses based on the above reality. While not going under its now ‘official’ title, many of the principles of ‘alternative development’ have been ingrained in policy responses and limitations over the past several centuries.